2005
DOI: 10.1210/en.2005-0402
|View full text |Cite
|
Sign up to set email alerts
|

Glucose Dependence of the Regulated Secretory Pathway in αTC1-6 Cells

Abstract: We have investigated the effects of chronically elevated glucose concentrations on the pancreatic alpha-cell line alphaTC1-6. We show that basal glucagon secretion and proglucagon gene expression were increased in response to high glucose levels. The extent of acute stimulated secretion of glucagon was also increased in response to high glucose, as was the transcription of the prohormone processing enzymes PC1/3 and PC2. The secretion of GLP-1, a proglucagon-derived peptide produced by cleavage of proglucagon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
59
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(65 citation statements)
references
References 53 publications
3
59
3
Order By: Relevance
“…One possibility is increased production or activity of PC1/3. Indeed it has been shown that PC1/3 is upregulated by high glucose in alpha cells [34] and in hyperglycaemic db/db mice [17]. Therefore, it is possible that this is also the mechanism in our studies.…”
Section: Discussionmentioning
confidence: 59%
“…One possibility is increased production or activity of PC1/3. Indeed it has been shown that PC1/3 is upregulated by high glucose in alpha cells [34] and in hyperglycaemic db/db mice [17]. Therefore, it is possible that this is also the mechanism in our studies.…”
Section: Discussionmentioning
confidence: 59%
“…It was concluded that insulin, unlike glucose, modulates glucagon expression. The lack of response to glucose was further confirmed in isolated rat islets (Gremlich et al 1997, Dumonteil et al 2000, contrasting with the up-regulation of glucagon expression observed in clonal a-cells (Dumonteil et al 1999, McGirr et al 2005. The effect of amino acids on glucagon gene regulation has also been studied.…”
Section: Glucagon Synthesismentioning
confidence: 95%
“…Lys 19 (mtt) was selectively deprotected using 2% trifluoroacetic acid, 5% triisopropylsilane in dichloromethane, followed by coupling to Cy5 succinimidyl ester (0.025 mmol, 19 mg) in the presence of N,N-diisopropylethylamine (0.6 mmol, 100 L). Once fully functionalized, Dpr 3 (octanoyl), Lys 19 (Cy5) ghrelin (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19) was cleaved from the resin using 95% trifluoroacetic acid, 2.5% triisopropylsilane and 2.5% water (2 mL). The crude peptide was precipitated using ice cold tert-butylmethylether (20 mL) and the dark blue crude solid was then isolated by centrifugation.…”
Section: Methodsmentioning
confidence: 99%
“…HEK 293 cells were transiently transfected with the cDNA encoding GHS-R1a in order to visualize the binding of Cy5-ghrelin (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19) in situ. Both wt HEK and HEK/GHS-R1a cells were plated at a density of 1 × 10 6 cells/well in a 6-well plate, and serum starved overnight.…”
Section: Live Imaging Of Cy5-ghrelin(1-19) In Hek293/ghs-r1a Cellsmentioning
confidence: 99%
See 1 more Smart Citation